Environmental Impact Assessment, on the Operation of Conventional and More Electric Large Commercial Aircraft - Seresinhe, R.; Lawson, Craig P.; Sabatini, Roberto (Cranfield University, 2013)
Global aviation is growing exponentially and there is a great emphasis on trajectory optimization to reduce the overall environmental impact caused by aircraft. Many optimization techniques exist and are being studied for this purpose. The CLEAN SKY Joint Technology Initiative for aeronautics and Air transport, a European research activity run under the Seventh Framework program, is a collaborative initiative involving industry, research organizations and academia to introduce novel technologies to improve the environmental impact of aviation. As part of the overall research activities, "green" aircraft trajectories are addressed in the Systems for Green Operations (SGO) Integrated Technology Demonstrator. This paper studies the impact of large commercial aircraft trajectories optimized for different objectives applied to the on board systems. It establishes integrated systems models for both conventional and more electric secondary power systems and studies the impact of fuel, noise, time and emissions optimized trajectories on each configuration. It shows the significant change in the fuel burn due to systems operation and builds up the case as to why a detailed aircraft systems model is required within the optimization loop. Typically, the objective in trajectory optimization is to improve the mission performance of an aircraft or reduce the environmental impact. Hence parameters such as time, fuel burn, emissions and noise are key optimization objectives. In most instances, trajectory optimization is achieved by using models that represent such parameters. For example aircraft dynamics models to describe the flight performance, engine models to calculate the fuel burn, emissions and noise impact, etc. Such techniques have proved to achieve the necessary level of accuracy in trajectory optimization. This research enhances previous techniques by adding in the effect of systems power in the optimization process. A comparison is also made between conventional power systems and more electric architectures. In the conventional architecture, the environmental control system and the ice protection system are powered by engine bleed air while actuators and electrics are powered by engine shaft power off-takes. In the more electric architecture, bleed off take is eliminated and the environmental control system and ice protection system are also powered electrically through engine shaft power off takes.